2022
DOI: 10.1021/acscatal.2c00718
|View full text |Cite
|
Sign up to set email alerts
|

Stereodivergent Synthesis of Epoxides and Oxazolidinones via the Halohydrin Dehalogenase-Catalyzed Desymmetrization Strategy

Abstract: Catalytic stereoselective desymmetrization of prochiral compounds to valuable chiral molecules is of interest in asymmetric synthesis. Here, we report the development of an efficient biocatalytic desymmetrization strategy for the stereodivergent synthesis of various chiral epoxides and oxazolidinones by the identification and engineering of halohydrin dehalogenases. The use of stereocomplementary halohydrin dehalogenases for the desymmetrization of 2-substituted-1,3-dichloro-2-propanols generates chiral epoxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 72 publications
0
26
0
Order By: Relevance
“…Their ability to also catalyze the reverse reaction (i. e. epoxide ring opening) with anionic C‐, N‐, O‐, S‐ and halide nucleophiles [3] provides divergent access to an impressive repertoire of valuable products [4–9] (Scheme 1). This catalytic promiscuity, combined with the diversity of sequences available from databases, has made HHDHs attractive biocatalysts for kinetic resolutions and desymmetrization reactions [10–12] . For instance, HHDHs have been employed for the synthesis of enantioenriched oxazolidinones, tertiary alcohols, epihalohydrins, and – more recently – cyclohexyl synthons, spiro‐epoxyoxindoles and benzylic alcohols [10,13–19] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their ability to also catalyze the reverse reaction (i. e. epoxide ring opening) with anionic C‐, N‐, O‐, S‐ and halide nucleophiles [3] provides divergent access to an impressive repertoire of valuable products [4–9] (Scheme 1). This catalytic promiscuity, combined with the diversity of sequences available from databases, has made HHDHs attractive biocatalysts for kinetic resolutions and desymmetrization reactions [10–12] . For instance, HHDHs have been employed for the synthesis of enantioenriched oxazolidinones, tertiary alcohols, epihalohydrins, and – more recently – cyclohexyl synthons, spiro‐epoxyoxindoles and benzylic alcohols [10,13–19] …”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] For instance, HHDHs have been employed for the synthesis of enantioenriched oxazolidinones, tertiary alcohols, epihalohydrins, and -more recently -cyclohexyl synthons, spiroepoxyoxindoles and benzylic alcohols. [10,[13][14][15][16][17][18][19] Despite the breadth of literature examples available for the application of HHDHs in asymmetric catalysis, these enzymes come with some limitations, which have thus far impeded their wider application in (chemo-)enzymatic synthesis. [12] Chief among these is their relatively specific substrate scope, which typically only includes terminal epoxides.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20]24,[32][33][34][35][36][37] Activity towards ortho-substituted SO is limited solely to an o-F (1a) derivative, as observed in this study and previously by others. [36][37][38][39] A larger substituent at this position might not allow placing of a ligand in a productive orientation. This prompted us to probe the activity of HheC towards the substrate bearing another valuable but larger fluorine containing substituent, the trifluoromethyl group at the ortho position.…”
Section: Substrate Scope and Enantioselectivity Of Hhecmentioning
confidence: 99%
“…Thus, the kinetic and thermodynamic parameters of the reaction can be expected to be different in HheC-M4 compared to HheC. 28 Recently, the HHDH-catalysed biotransformation of 2-substituted-1,3-dichloro-2-phenylpropan-2-ols to oxazolidinones was reported by Wan et al 39 The variant HheC-M4 was found to be the most efficient catalyst for the synthesis of (S)-oxazolidinones in terms of enantioselectivity (ee = 85 → 99%). Since the conversion of bulky substrates has been troublesome for this group of enzymes, optimizing the activity and enantioselectivity of HHDHs in this regard is appreciated.…”
Section: Papermentioning
confidence: 99%
“…Previously, our group reported a series of studies concerning novel P450 enzymes for enantioselective benzylic hydroxylation 21 and asymmetric sulfoxidation, 22 engineered halohydrin dehalogenases for stereodivergent synthesis of epoxides and oxazolidinones, 23 aldoxime dehydratases 24 and light-promoted direct fluoroalkylation. 25 Recently, the direct photocatalytic C–H oxyfunctionalization of aromatic hydrocarbon with O 2 to access the corresponding ketones has been developed rapidly, using different organic dyes including sodium anthraquinonesulfonate (SAS).…”
Section: Introductionmentioning
confidence: 99%